Analysis of the Impact of Social Forestry in Achieving Conflict Resolution and Sustainable Natural Rubber Management - Case Studies of Social Forestry in Jambi and East Kalimantan - Rafiq, Yasmine Sagita; Sofilda, Eleonora (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This research focuses on agrarian conflict resolution strategies with an Alternative Dispute Resolution (ADR) approach through Social Forestry in this case with the Forestry Partnership scheme in Jambi HTI concession areas and in East Kalimantan HTI concessions. The purpose of this study is to analyze conflict typologies related to sustainable natural rubber management in Jambi and in East Kalimantan, and conflict resolution strategies with forestry partnership methods as a form of Alternative Dispute Resolution approach. In addition, this study also analyzes the relationship of Social Forestry to Sustainable Development Goals (SDGs) and its impact on related parties. The main design of this study uses a qualitative approach. Data collection in this study was carried out through observation techniques, Focus Group Discussion (FGD), in-depth interviews, and secondary data. With purposive sampling techniques to communities who have partnered and who have not partnered with the company and company stakeholders. The results showed that agrarian conflicts in East Kalimantan and Jambi were relatively the same but with different scales, with the main problem most often encountered being land disputes between companies holding concession permits and communities that have had success in land management. The approach used by the company in conflict resolution is through Alternative Dispute Resolution (ADR) through the Social Forestry program under the Forestry Partnership scheme. Social forestry under the Forestry Partnership scheme has important significance and is relatively acceptable to the parties. The main impact of the Forestry Partnership is a reduction in conflict pressure between the two sides, stability in business and improved livelihoods for the community.